Endosomal transport of septin mRNA and protein indicates local translation on endosomes and is required for correct septin filamentation. (16th December 2013) - Baumann, Sebastian; König, Julian; Koepke, Janine; Feldbrügge, Michael
Abstract Endosomes transport lipids and proteins over long distances by shuttling along microtubules. They also carry mRNAs on their surface, but the precise molecular function of this trafficking process is unknown. By live cell imaging of polarized fungal hyphae, we show microtubule‐dependent transport of septin mRNA and encoded septin protein on the same shuttling endosomes. Consistent with the hypothesis that septin mRNA is translated on endosomes, the accumulation of septin protein on endosomes requires the recruitment of septin mRNA. Furthermore, ribosomal proteins co‐localise with shuttling endosomes, but only if mRNA is present. Importantly, endosomal trafficking is essential for an efficient delivery of septin protein to filaments at growth poles, a process necessary to establish unipolar growth. Thus, we propose that local mRNA translation loads endosomes with septins for assembly and efficient delivery to septin filaments.